Explosive - Meyer, Rudolf; Kohler, Josef; Homburg, Axel
"This reference work has been enlarged and updated without tampering with its tried and tested format. Around 500 alphabetically ordered, monographic entries consider the physicochemical properties, production methods and safe applications of over 120 explosive chemicals; discuss 70 fuels, additives and oxidizing agents; and describe test methods." "The extensive thermodynamic data have been thoroughly updated and for the first time are also provided in electronic format. The included CD-ROM was compiled by the Fraunhofer Institute of Chemical Technology (Pfinztal, Germany) and represents an excerpt from the ICT Thermodynamical Database. Not only additional thermodynamic data, and references to further reading, but also enhanced search facilities are provided." "Other key features include: the 1500-entry combined index and glossary (comprising terms and abbreviations in English, French and German), conversion tables and many literature references." "This book is suitable for explosive experts and also for translators, public authorities and patent lawyers."--BOOK JACKET.